Model Pengelolaan Zakat Saham dan Investasi di Baznas (Bazis) Provinsi DKI Jakarta - Fajria Nur Fitri; Mira Rahmi (Journal of Islamic Economics and Finance Studies, 2021)
AbstractIndonesia is one of the most populous Muslim countries, so it has a very large potential for zakat. The types of zakat in Indonesia are zakat fitrah and zakat maal, over time zakat maal has developed what is known as contemporary zakat in the form of professional zakat, stock zakat, investment zakat, deposit zakat and the like. Each type of zakat collected is expected to have the potential to improve the economy and prosper the people. Zakat shares in Indonesia have the distribution of funds from companies or individuals based on the results of company profits and share profits where this profit is given to mustahik. So from this research on the management of stock and investment zakat, the authors found that related problems are still found to be low awareness of shareholders and investors to pay their zakat. This study aims to explain the management model of stock and investment zakat, and analyze the stock and investment zakat program in Baznas DKI Jakarta Province. The method used is a qualitative descriptive approach, the data sources used are through previous research, books, and the results of interviews with resource persons who understand zakat shares and investments. The results obtained by Baznas DKI Jakarta Province in managing stock and investment zakat using the theory of Yusuf Qardhawi and in an effort to increase muzakki or investors of Baznas DKI Jakarta Province. AbstrakIndonesia merupakan salah satu negara berpenduduk muslim terbesar, sehingga memiliki potensi zakat yang sangat besar. Jenis-jenis zakat yang ada di Indonesia adalah zakat fitrah dan zakat maal, seiring berjalannya waktu zakat maal telah berkembang yang dikenal dengan istilah zakat kontemporer berupa zakat profesi, zakat saham, zakat investasi, zakat deposito dan sejenisnya. Setiap jenis zakat yang terkumpul diharapkan memiliki potensi untuk meningkatkan perekonomian dan mensejahterakan umat. Zakat saham di Indonesia memiliki pembagian dana dari perusahaan atau perorangan berdasarkan hasil keuntungan perusahaan dan keuntungan bagi hasil dimana keuntungan ini diberikan kepada mustahik. Maka dari penelitian tentang pengelolaan zakat saham dan investasi ini, penulis menemukan permasalahan terkait masih rendahnya kesadaran pemegang saham dan investor untuk membayar zakatnya. Penelitian ini bertujuan untuk menjelaskan model pengelolaan zakat saham dan investasi, serta menganalisis program zakat saham dan investasi di Baznas Provinsi DKI Jakarta. Metode yang digunakan adalah pendekatan deskriptif kualitatif, sumber data yang digunakan adalah melalui penelitian terdahulu, buku, dan hasil wawancara dengan nara sumber yang memahami zakat saham dan investasi. Hasil yang diperoleh Baznas Provinsi DKI Jakarta dalam mengelola zakat saham dan investasi menggunakan teori Yusuf Qardhawi dan dalam upaya meningkatkan muzakki atau investor Baznas Provinsi DKI Jakarta.